Censorship Towards the Subject of the Warsaw Uprising in Belles-Lettres in 1956–1958 - Kloc, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Right from the beginning, the subject of the Warsaw Uprising was often manipulated or even entirely erased from public discourse under the Stalinist regime. It was only after the liberalization of culture and the easing of censorship-related repressions that the said topic returned in literature. The paper focuses on the censorship bureau’s approach to the image of the Uprising presented by writers. Moreover, it attempts to specify – on the basis of specific examples – the kind of content that was accepted, rejected or amended. The juxtaposition of censors’ documents and the content of the published works allows for the examination of the depth of censors’ interventions and their methods of manipulating historical facts. Those areas of special interest include: presentation of the division among the insurgents who were supposed to belong either to the brave ordinary soldiers or the passive leadership, as well as the attitude towards the People’s Army, the First Polish Army, the Home Army or the Red Army, with special regard for its passiveness during the Uprising.